Mr. Pusskins and Little Whiskers : another love story - Lloyd, Sam. (New York : Atheneum Books for Young Readers, 2008)
When Emily brings home a little kitten to be best friends with Mr. Pusskins, the older cat does not appreciate the gesture.
Kirkus Review
School Library Journal
2.0
K-3.
K-3
Keywords: Cats -- Juvenile fiction; Cats -- Fiction; Cats -- Fiction